Análise do uso de conversor de frequência na ventilação forçada de sistemas de resfriamento evaporativo visando à eficiência energética - Fonseca, André Luiz Amorim da (2012)
This dissertation is meant to examine the use of frequency converters that trigger a induction machine coupled with a forced ventilation system of the direct evaporative cooller. It compares the use of the drive and start directly in the system to verify the electrical efficiency of the system. Once the tariff structure itself during the dry period has a direct influence of the characteristic matrix of hydroelectric power generation and seasonality, which decreases its potential substantially during this period, the use of adiabatic evaporative cooling systems becomes more energy efficient than air conditioners during this period, and can provide improved thermal comfort. By varying the rotation speed of the fan with the drive this type of system has increased its efficiency. The analysis of the set is also made by observing the influence on the effective temperature and relative humidity. Data were collected in the field, shed with 3 adequate evaporative cooling systems. The results obtained from alternative strategies or automation system with the use of programmer time and sensors are simulated and compared together with the air conditioner (simulated in Energy Plus) in seasonal mixed systems, with the use of evaporative cooling in dry and air conditioner in wet period of the year.